2017
DOI: 10.1021/acs.inorgchem.7b01793
|View full text |Cite
|
Sign up to set email alerts
|

Mn3 Single-Molecule Magnets and Mn6/Mn9 Clusters from the Use of Methyl 2-Pyridyl Ketone Oxime in Manganese Phosphinate and Phosphonate Chemistry

Abstract: The syntheses, structures, and magnetochemical properties are reported for five new Mn clusters: [MnO(OPPh)(mpko)](ClO) (1), [MnO(OPPh)(ppko)](ClO) (2) [MnO(OMe)(OPPh)(mpko)](ClO) (3), [MnMnO(OCMe)(OPPh)(mpko)(HO)] (4), and [MnMnO(mpko)(HO)(ClO)](ClO) (5), where mpko (or ppko) is the anion of methyl (or phenyl) 2-pyridyl ketone oxime. 1 was obtained by carboxylate substitution on [MnO(OCMe)(mpko)](ClO) by treatment with diphenylphosphinic acid (PhPOH). The comproportionation reaction between Mn(ClO) and NBuMnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 77 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…The fitting of χ M of polynuclear magnetic compounds was a nontrivial issue, especially for manganese [ 39 ], in view of the overparameterization problem. We then decided to use an in-house software, based on full Hamiltonian diagonalization and Levenberg-Marquardt optimization, by first fitting χ M T data to the sum of two terms: ( i ) a Hamiltonian containing the isotropic exchange and Zeeman terms for the coupled dinuclear species, as reported in Equation (6), and ( ii ) the Zeeman term for the molar uncoupled fraction f [ 40 ], further augmented with a TIP component fixed at 600 × 10 −6 emu mol −1 , value typical for manganese(III) ions [ 41 ]. The best-fit parameters revealed to be relatively insensitive to the TIP value.…”
Section: Resultsmentioning
confidence: 99%
“…The fitting of χ M of polynuclear magnetic compounds was a nontrivial issue, especially for manganese [ 39 ], in view of the overparameterization problem. We then decided to use an in-house software, based on full Hamiltonian diagonalization and Levenberg-Marquardt optimization, by first fitting χ M T data to the sum of two terms: ( i ) a Hamiltonian containing the isotropic exchange and Zeeman terms for the coupled dinuclear species, as reported in Equation (6), and ( ii ) the Zeeman term for the molar uncoupled fraction f [ 40 ], further augmented with a TIP component fixed at 600 × 10 −6 emu mol −1 , value typical for manganese(III) ions [ 41 ]. The best-fit parameters revealed to be relatively insensitive to the TIP value.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent paper, Geng et al [166] showed that the magnetoelectric force microscopy (MeFM) that is a combination of magnetic force microscopy (MFM) with in situ modulated electric fields (E), can be employed to detect the E-induced magnetization (ME) and to show the multiferroic domain structure in hexagonal (h-)ErMnO 3 . Along with multiferroic materials (e.g., Cu 2 OSeO 3 ) [167], they exhibit the so-called magnetoelectric effect, in which an external magnetic field can cause electric polarization and an electric field can cause magnetic ordering. The field of the manipulation of magnetic structures by electrical fields is beyond the scope of this review, but it is highly desirable for technological applications.…”
Section: Magnetic Force Microscopy (Mfm)mentioning
confidence: 99%
“…The former [142][143][144][145][146][147][148][149][150][151][152][153][154][155] have led to a variety of clusters with exciting molecular structures and magnetic properties; they have been used, among others, in the development of a synthetic process widely known as "ground-state spin switching and enhancing SMM properties via targeted structural distortion" strategy [56,[142][143][144][145][147][148][149]. The latter [156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174], in addition to their involvement in the synthesis of 3d-metal SIMs [158], have provided access to interesting 3d-metal clusters and SMMs. They have also been used in the realization of a synthetic scheme best known as "'switching on' SMM properties upon conversion of low-spin complexes into high-spin ones without changing the core" strategy [168,169] and, when derivatized by design, in the development of an innovative approach which allows the covale...…”
Section: Molecular and Supramolecular Approaches In The Chemistry Of Manganese Smms Using Simple And Elaborate 2-pyridyl Oximesmentioning
confidence: 99%
“…The rational design and synthesis of metal phosphinates has garnered great attention from many researchers relating to chemistry and materials science due to their application in various fields. For instance, a cuboidal tetranuclear manganese constructed with diphenyl­phosphinic acid can act as an oxygen evolving complex for water oxidation in photosystem II . A cobalt compound built with a racemic phosphonate ligand can exhibit both polarity and ferromagnetism .…”
Section: Introductionmentioning
confidence: 99%